Parameters and universals - Kayne, Richard S. (Oxford studies in comparative syntax., 2000)
This is a collection of previously published essays on comparative syntax by the distinguished linguist Richard Kayne. The papers cover issues of comparative syntax as they are applied to French, Italian, and other Romance languages and dialects, together forming a strongly cohesive set that will be valuable to both scholars and students.